Dramatic Tuning of the Topological Hall Effect in AxRhO2 (A = K, Rb, and Cs) Crystals by Electron Concentration or Cation. (26th December 2022) - Lv, Yang‐Yang; Zhang, Bin‐Bin; Li, Xiao; Lin, Dajun; Yao, Shu‐Hua; Xiong, Ye; Zhou, Jian; Chen, Y. B.; Weng, Hongming; Shi, Y. G.; Lu, Ming‐Hui; Chen, Yan‐Feng
Abstract: Topological Hall effect, being an unconventional anomalous Hall effect, is originated from the real‐space Berry curvature caused by the nontrivial topological spin textures in materials. Manipulations of nontrivial magnetic structure and related topological Hall effect are very important for the study of the chiral magnet. Herein, it is experimentally observed that the significant topological Hall conductivity σ xy in antiferromagnetic K0.5 RhO2 can reach 3.5% of ν = 1 quantum conductivity below 20 K. Furthermore, by adjusting the concentration of K‐cation different from 0.5 in Kx RhO2 or substituting the K cations by Rb or Cs to form Rb0.5 RhO2 or Cs0.5 RhO2, it is observed that the topological Hall effect is much weakened or even disappeared. This evolution, verified by the theoretical calculations, is attributed to the unstable ground state of the non‐coplanar spin structure in Kx RhO2 ( x  = 0.4 and 0.6) and Cs0.5 RhO2 . The significantly tunable topological Hall effect in Ax RhO2 makes it prospective on logical/sensor devices of spintronics. Abstract : A significant topological Hall effect is observed in K0.5 RhO2 crystals with Hall conductivity up to 3.5% of the quantum conductivity. This effect is dramatically suppressed or even disappears when the concentration of K deviates from 0.5 or K is replaced by Rb/Cs. Theoretical calculations show that the topological Hall effect is originated from non‐coplanar spin textures in K0.5 RhO2 .